Physical Modeling on Local Scour at Complex Piers - Amini, Seyed Ata (2009)
Over the past decades, great strides have been made in the ability to accurately predict design scour depths at simple bridge pier structures. While, many bridge piers are complex in shape, consisting of several components (e.g., column, pile cap and pile group). There is a general lack of confidence in available methods for predicting local scour at complex piers. The main objective of the research is to provide accurate estimating of geometrical characteristics of complex pier and its location relative to undisturbed streambed on scour depth, for improving existing scour prediction methods. Furthermore, the collected data can fill voids in existing data for pier with complex geometries in various locations. In this research, an experimental study on multiple piles and complex piers and its components were conducted. The variables investigated were the dimensions of complex piers and the models location relative to initial streambed. In addition, in the experiments on pile group, the pile spacing, arrangement and submergence ratio were examined. A wide range of experiments on individual components including pile group, pile cap and column and combination of these components such as the column mounted on the pile cap and complex piers were studied. Flow conditions and sediment characteristics were kept constant for all of the experiments. The flow discharge, water depth and flow velocity readings were taken using an Area Velocity Module (AVM). Cohesionless uniform sediment was used with the mean particle sizes, d50=0.8 mm and geometric standard deviation of particles, σg=1.34. The experiments were performed under clear-water conditions at threshold flow intensity. The results of experiments on individual components were used to present new methods to predict local scour at pile group, pile cap and column, which is useful to be used for predicting scour at multiple piles and complex piers. Outcomes of verifying these methods show that proposed methods give reasonable scour depth prediction. In addition, it was found that, besides the parameters that affect scour at a uniform pier, the scour depth at complex piers and its components are highly depend on their locations relative to initial streambed. The experimental data obtained on complex pier models was used to evaluate predictions of existing methods. Federal Highway Administration, Hydraulic Engineering Circular No. 18, HEC-18, Florida Department of Transportation, FDOT and Coleman methods for complex piers, were examined. It was found that the results of HEC-18 method have a much larger scatter than FDOT and Coleman methods. In addition, the measured scour depths produced by isolated components were used to evaluate superposition methodology. The upshots indicate that this methodology do not accurately predict the observed scour depth at composite structures.